Quizartinib versus salvage chemotherapy in relapsed or refractory FLT3-ITD acute myeloid leukaemia (QuANTUM-R): a multicentre, randomised, controlled, open-label, phase 3 trial - Cortés, Jorge Eduardo; Khaled, Samer; Martinelli, Giovanni; Perl, Alexander E; Ganguly, Siddhartha; Russell, Nigel; Krämer, Alwin; Dombret, Hervé; Hogge, Donna; Jonas, Brian A; Leung, Anskar Yu-Hung; Mehta, Priyanka; et al. (The lancet. Oncology, 2019)
Background: Patients with relapsed or refractory FLT3 internal tandem duplication (FLT3-ITD)-positive acute myeloid leukaemia have a poor prognosis, including high frequency of relapse, poorer response to salvage therapy, and shorter overall survival than those with FLT3 wild-type disease. We aimed to assess whether single-agent quizartinib, an oral, highly potent and selective type II FLT3 inhibitor, improves overall survival versus salvage chemotherapy. Methods: QuANTUM-R is a randomised, controlled, phase 3 trial done at 152 hospitals and cancer centres in 19 countries. Eligible patients aged 18 years or older with ECOG performance status 0-2 with relapsed or refractory (duration of first composite complete remission ≤6 months) FLT3-ITD acute myeloid leukaemia after standard therapy with or without allogeneic haemopoietic stem-cell transplantation were randomly assigned (2:1; permuted block size of 6; stratified by response to previous therapy and choice of chemotherapy via a phone-based and web-based interactive response system) to quizartinib (60 mg [30 mg lead-in] orally once daily) or investigator's choice of preselected chemotherapy: subcutaneous low-dose cytarabine (subcutaneous injection of cytarabine 20 mg twice daily on days 1-10 of 28-day cycles); intravenous infusions of mitoxantrone (8 mg/m2 per day), etoposide (100 mg/m2 per day), and cytarabine (1000 mg/m2 per day on days 1-5 of up to two 28-day cycles); or intravenous granulocyte colony-stimulating factor (300 μg/m2 per day or 5 μg/kg per day subcutaneously on days 1-5), fludarabine (intravenous infusion 30 mg/m2 per day on days 2-6), cytarabine (intravenous infusion 2000 mg/m2 per day on days 2-6), and idarubicin (intravenous infusion 10 mg/m2 per day on days 2-4 in up to two 28-day cycles). Patients proceeding to haemopoietic stem-cell transplantation after quizartinib could resume quizartinib after haemopoietic stem-cell transplantation. The primary endpoint was overall survival in the intention-to-treat population. This trial is registered with ClinicalTrials.gov, number NCT02039726, and follow-up is ongoing. Findings: Between May 7, 2014, and Sept 13, 2017, 367 patients were enrolled, of whom 245 were randomly allocated to quizartinib and 122 to chemotherapy. Four patients in the quizartinib group and 28 in the chemotherapy group were not treated. Median follow-up was 23·5 months (IQR 15·4-32·3). Overall survival was longer for quizartinib than for chemotherapy (hazard ratio 0·76 [95% CI 0·58-0·98; p=0·02]). Median overall survival was 6·2 months (5·3-7·2) in the quizartinib group and 4·7 months (4·0-5·5) in the chemotherapy group. The most common non-haematological grade 3-5 treatment-emergent adverse events (within ≤30 days of last dose or >30 days if suspected to be a treatment-related event) for quizartinib (241 patients) and chemotherapy (94 patients) were sepsis or septic shock (46 patients [19%] for quizartinib vs 18 [19%] for chemotherapy), pneumonia (29 [12%] vs eight [9%]), and hypokalaemia (28 [12%] vs eight [9%]). The most frequent treatment-related serious adverse events were febrile neutropenia (18 patients [7%]), sepsis or septic shock (11 [5%]), QT prolongation (five [2%]), and nausea (five [2%]) in the quizartinib group, and febrile neutropenia (five [5%]), sepsis or septic shock (four [4%]), pneumonia (two [2%]), and pyrexia (two [2%]) in the chemotherapy group. Grade 3 QT prolongation in the quizartinib group was uncommon (eight [3%] by central reading, ten [4%] by investigator report); no grade 4 events occurred. There were 80 (33%) treatment-emergent deaths in the quizartinib group (31 [13%] of which were due to adverse events) and 16 (17%) in the chemotherapy group (nine [10%] of which were due to adverse events). Interpretation: Treatment with quizartinib had a survival benefit versus salvage chemotherapy and had a manageable safety profile in patients with rapidly proliferative disease and very poor prognosis. Quizartinib could be considered a new standard of care. Given that there are only a few available treatment options, this study highlights the value of targeting the FLT3-ITD driver mutation with a highly potent and selective FLT3 inhibitor. Funding: Daiichi Sankyo.
Gesehen am 02.09.2019